2021
DOI: 10.1177/01617346211017462
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound Imaging of Uterine Disorders: A Systematic Review

Abstract: Uterine disorders are often presented with overlapping symptoms. The microvasculature holds specific information important for diagnosing uterine disorders. Conventional sonography is an established diagnostic technique in gynecology, but is limited by its inability to image the microvasculature. Contrast-enhanced ultrasound (CEUS), is capable of imaging the microvasculature by means of intravascular contrast agents; that is, gas-filled microbubbles. We provide a literature overview on the use of CEUS in diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 57 publications
(134 reference statements)
0
13
0
Order By: Relevance
“…Clinically, HIFU could be used as an effective auxiliary method to treat uterine sarcoma without increasing the risk of tumor metastasis. Until now, HIFU has only been reported as a means to ablate leiomyosarcoma that is presumed to be a fibroid in clinical gynecologic practice (10). The HIFU ablation may have a positive effect on the prognosis of uterine leiomyosarcoma and result in a lower risk of dissemination and improved survival outcomes (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, HIFU could be used as an effective auxiliary method to treat uterine sarcoma without increasing the risk of tumor metastasis. Until now, HIFU has only been reported as a means to ablate leiomyosarcoma that is presumed to be a fibroid in clinical gynecologic practice (10). The HIFU ablation may have a positive effect on the prognosis of uterine leiomyosarcoma and result in a lower risk of dissemination and improved survival outcomes (9).…”
Section: Discussionmentioning
confidence: 99%
“…While HIFU directly ablates lesions, the ablated tissue induces the production of anti-tumor antibodies against the released tumor antigens, which has subsequent antitumor immune effects. However, at present, there are few reports on the application of HIFU ablation of uterine sarcoma before surgery (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions of different studies regarding the CEUS presentation of adenomyosis are not uniform, and relevant literature showing increased temporal variability of the lesion is lacking ( 23 ). A previous study has suggested that typical uterine leiomyoma is characterized by a ring of hyperenhancement around the tumor, with uniform or uneven enhancement of the entire tumor and a clear demarcation from the normal muscle layer ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular perfusion of a uterus can be quantitatively calculated using parameters such as the wash-in phase, peak intensity, and the wash-out phase to create an interpretable time-intensity curve. 4 Qualitatively, the technology allows the observer to visualize perfusion in real-time, and any differential perfusion might point to differential arterial inflow to the allograft. Prior nontransplant studies of uterus perfusion following uterine artery embolization 5,6 demonstrated that contrast-enhanced ultrasound can assess the degree of perfusion following embolization, and these ultrasounds showed good agreement with both MRI and angiograms.…”
Section: Arterial Perfusion-contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…Contrast-enhanced ultrasound technology is another diagnostic imaging technology that may have an increased role in the immediate postoperative assessment of uterus transplant allografts. Contrast-enhanced ultrasound administers intravenous contrast agents made of microbubbles or nanobubbles of gas, which enhances visualization of the macrovasculature and microvasculature 4. When these microbubble contrast agents are injected, they remain intravascular, and when the uterus is imaged with either a transvaginal or transabdominal probe, the bubbles oscillate to produce an observable echo image.…”
Section: Technological Advancement: Diagnostic Imagingmentioning
confidence: 99%